PERANCANGAN PROMOSI ES DURIAN GANTI NAN LAMO MELALUI SURAT KABAR - DEWI WAHYUNI, Ir. Drs. Heldi, M.Si, San Ahdi, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
The emphasis of this design directed for culinary products of Es Durian at pondok. The development of Es Durian leads business competition for consumer attention at pondok. The issue of es durian brand Ganti Nan Lamo opposite with Es durian Iko Gantinyo turns out to have the same effort. Though, the pioneer of Es durian is Es durian Ganti Nan Lamo.The main goal of design that is to inform and to communicate the promotion of Es durian Ganti Nan Lamo for consumer through Visual Communication Design which are effective and efficient so that it can fulfill consumer need. Media supporters are designed to enhance society awareness towards Es durian Ganti Nan Lamo. In factors identification that happens in internal and external, the author uses 5W+1H method to approach better parameter with brainstorming as analysis basic.Through the promotion design Es durian Ganti Nan Lamo by newspaper, it can raise the sales and society will know the existence of Es durian Ganti Nan Lamo.Keywords: Design, Promotion, Newspaper.